1996
DOI: 10.1128/jcm.34.2.249-253.1996
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PCR detection of mecA with standard susceptibility testing methods to determine methicillin resistance in coagulase-negative staphylococci

Abstract: Approximately 75% of coagulase-negative staphylococci are resistant to methicillin, but it is suspected that even more resistance exists that is not detected by standard susceptibility assays. To determine the most accurate assay for measuring resistance, we compared the detection of mecA by PCR with detection by National Committee for Clinical Laboratory Standards methods using oxacillin as the class drug. Strains from 11 species of coagulase-negative staphylococci were selected such that 84% were susceptible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
2
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 23 publications
3
54
2
1
Order By: Relevance
“…It is likely that resistance is not expressed in these strains, despite the presence of sequences corresponding to the mecA gene in the bacterial chromosome. On the contrary, speci®cities obtained with the same tests were lower than those reported by other groups (Geha et al 1994;Mulder 1996;York et al 1996;Kohner et al 1999). This observation suggests that our CNS population has an abnormally high prevalence of mecA-independent methicillin resistance.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…It is likely that resistance is not expressed in these strains, despite the presence of sequences corresponding to the mecA gene in the bacterial chromosome. On the contrary, speci®cities obtained with the same tests were lower than those reported by other groups (Geha et al 1994;Mulder 1996;York et al 1996;Kohner et al 1999). This observation suggests that our CNS population has an abnormally high prevalence of mecA-independent methicillin resistance.…”
Section: Discussioncontrasting
confidence: 44%
“…When compared with several previous studies (Geha et al 1994;York et al 1996;Kohner et al 1999), both the disc diffusion and the agar dilution tests showed signi®cant increases in sensitivity (Table 2). These improvements are largely due to the use of the new NCCLS guidelines (NCCLS 2000a, b) which provide more accurate criteria to evaluate methicillin resistance through these phenotypic assays.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The detection of methicillin resistance in staphylococci is complex and di⁄culties exist in accurately identifying MRS mainly because the resistance is often heterogeneous and its expression is a¡ected by di¡erent factors [3]. A number of methods have been studied to detect methicillin resistance in both S. aureus and S. epidermidis, but contradictory results have been reported [4,18,19]. In this study, most isolates (95.3%) showed complete concordance among E-test, mecA PCR (revealed by generation of a single 533-bp fragment) and PBP2P (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of an additional low-affinity penicillinbinding protein 2a (PBP2a), which is encoded by the mecA gene, is associated with methicillin resistance in both S. aureus and CoNS (12,(15)(16)(17)(18)(19). Polymerase chain reaction (PCR) to detect the mecA gene as a rapid method for the identification of MRSA has been amply demonstrated (11,(20)(21)(22)(23)(24)(25)(26)(27). Some even consider PCR to be the method of choice for identifying MRSA and other methicillinresistant staphylococci (8,(28)(29)(30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%